Privacy preserving cloud data sharing system with flexible control. (August 2018) - Fang, Liming; Ge, Chunpeng; Huang, Zhiqiu; Wang, Jiandong
Abstract: With the development of cloud technology, sharing date between users securely becomes more and more important. Moreover, the cloud server should provide a flexible control on sharing date. This work presents a notion named fuzzy conditional broadcast proxy re-encryption (FC-BPRE), in which a semi-honest proxy can transform a delegator's ciphertext to a new ciphertext for a set of delegatees when the ciphertext satisfies a certain condition set by the delegator. However, the proxy cannot learn any useful information about the underlying plaintext. The proxy can convert a ciphertext, encrypted under a condition set W, to a ciphertext encrypted under a condition set W ′ using a broadcast re-encryption key, if and only if S and S ′ are close to each other. We first formalize the notion of FC-PBRE scheme and then proposed a construction.